Determination of serum KIM-1 in patients with chronic kidney injury - Bansal, Abhishek; Nigoskar, Shreya (Asian Journal of Medical Sciences, 2023)
Background: Chronic kidney disease (CKD) affects more than 800 million people worldwide and is one of the leading non-communicable causes of death. Despite being a latent issue, once renal damage has started, the disease can rapidly progress to an advanced stage. Aims and Objectives: Currently, the most commonly used markers for the diagnosis of renal disease are non-specific and insensitive. As a result, the goal of the current study is to investigate whether KIM-1 could be a precise and sensitive biomarker for identifying early kidney injury in CKD patients. Materials and Methods: This case–control study recruited 155 participants from the Index Medical College Hospital v Research Centre, Indore, Madhya Pradesh, based on inclusion and exclusion criteria. 150 non-CKD subjects matched for age and sex were also taken from the hospital. The levels of KIM-1 were compared between CKD and non-CKD participants. Serum creatinine, urea, and creatinine clearance were also measured. Results: The levels of KIM-1 were substantially higher in CKD patients than in non-CKD participants. In addition, a negative relationship between KIM-1 and creatinine clearance was observed with a P<0.05. Conclusion: KIM-1 is a precise and sensitive kidney injury biomarker that can identify early kidney injury in CKD and contribute to the progression of interstitial fibrosis in kidney disease.